Drugs and the Death Penalty - Dresser, Rebecca (The Hastings Center report, 2014)
In October 2013, Missouri officials abandoned a plan to execute a convicted murderer using a novel method—an injection of propofol. The name of this drug became a household word after propofol played a role in singer Michael Jackson's death, but this has been a popular therapeutic drug for many years. Clinicians use it in intensive care, surgery, and common procedures like colonoscopy. After deciding to halt the execution, Missouri governor Jay Nixon told corrections officials to come up with a different lethal injection protocol. But that was not a simple assignment. Missouri had proposed using propofol because officials had faced barriers to obtaining the drugs previously used for executions. Corrections officials in death penalty states are finding it harder to secure drugs for lethal injection.